In-situ composite co-mo-cu-based phosphide oxide prismatic self-supporting electrocatalyst, and preparation method and application thereof
Patent Information
- Application Number
- CN202611245854.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-09
AI Technical Summary
上述技术表明,以HMF氧化反应替代析氧反应并与析氢反应耦合具有可行性,但现有方案所采用的电极活性组分和阴、阳极配置各有侧重,对于由同一种非贵金属自支撑材料同时承担析氢和HMF氧化催化功能,仍有进一步改进的需要
本发明以泡沫铜为导电基底,通过水热反应使Co-Mo-Cu复合氧化物前驱体直接在泡沫铜表面原位生长,再对负载有前驱体的泡沫铜进行气相磷化处理,所得催化剂可直接作为工作电极使用,无需将催化剂粉末与粘结剂、导电添加剂制成浆料后再行涂覆。由此,活性物质与导电基底之间形成一体化连接,有利于缩短电子传输路径并减少涂覆界面产生的附加接触阻力;结合粉末涂覆型对比例的性能结果以及实施例2在约-100 mA cm-2电流密度下连续析氢25 h电流基本稳定的测试结果,表明该自支撑电极构型能够兼顾电催化活性和连续工作稳定性。
Smart Images

Figure CN122879751A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrocatalytic biomass high-value utilization technology, and in particular to an in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst, its preparation method and application. Background Technology
[0002] Hydrogen energy boasts diverse sources and clean end-use processes. Water electrolysis, which converts water into hydrogen using renewable electricity, is a crucial technological route for converting electrical energy into chemical energy. Conventional water electrolysis systems typically consist of a hydrogen evolution reaction at the cathode and an oxygen evolution reaction at the anode. The oxygen evolution reaction involves multiple electron transfers and intermediate conversions, resulting in relatively slow reaction kinetics. It usually requires a high anode potential, increasing the operating voltage and energy consumption of the electrolyzer. Furthermore, the added value of the oxygen generated at the anode is relatively limited, hindering further improvements in the overall economic efficiency of the electrolysis process.
[0003] Replacing the anodic oxygen evolution reaction with an electrocatalytic oxidation reaction of small organic molecules, and coupling it with the cathode hydrogen evolution reaction, is a technical approach to reduce the burden on the anodic reaction and simultaneously achieve high-value conversion of organic matter. 5-Hydroxymethylfurfural (HMF) is a platform compound derived from biomass resources. Its molecule contains hydroxymethyl and aldehyde groups and can be selectively oxidized to 2,5-furandicarboxylic acid (FDCA). FDCA can be used as a bio-based polyester monomer. Therefore, combining the HMF electrocatalytic oxidation reaction with the hydrogen evolution reaction in the same electrolysis system allows for simultaneous anodic organic matter conversion and cathode hydrogen production.
[0004] Existing technologies have explored the coupling of HMF electrocatalytic oxidation and hydrogen evolution reaction. For example, patent publication CN110205645 A discloses an electrolysis device and reaction method using HMF electrooxidation as the anode reaction, which combines anode HMF oxidation with cathode hydrogen evolution through a dual-chamber electrolysis system. Patent publication CN 112538636 A discloses a method for preparing FDCA through electrocatalytic HMF oxidation and simultaneously producing hydrogen by water electrolysis, in which an integral electrode loaded with nitrogen-doped carbon-coated cobalt tetroxide nanowires is used as the anode. The above technologies show that it is feasible to replace the oxygen evolution reaction with HMF oxidation and couple it with the hydrogen evolution reaction. However, the electrode active components and anode and cathode configurations used in existing schemes have different focuses. Further improvements are still needed for the same non-precious metal self-supporting material to simultaneously undertake the catalytic functions of hydrogen evolution and HMF oxidation.
[0005] To reduce the cost of using precious metal catalysts, transition metal oxides, hydroxides, phosphides, and their composites are used in water electrolysis reactions. Patent CN 112774704 A discloses a foamed nickel self-supporting FeCo phosphide electrocatalyst. This involves obtaining a monolithic electrode by in-situ generation of a precursor on the surface of the foamed nickel followed by phosphating, demonstrating that the combination of in-situ growth and phosphating can be used to construct binder-free transition metal phosphide electrodes. Cobalt-molybdenum oxides offer the advantage of tunable multi-metal composition, but their conductivity and utilization of effective active sites may still limit their electrocatalytic performance. Introducing a phosphide phase to form a phosphide-oxide composite structure holds promise for improving the electrode's electron transport and surface reaction characteristics.
[0006] Therefore, a non-precious metal electrocatalytic material suitable for alkaline media is still needed, which can form a stable self-supporting structure on a conductive substrate to reduce the adverse effects of binders and particle contact interfaces in powder-coated electrodes on electron transport and active site utilization. At the same time, it is necessary to rationally control the multi-metal composition, microstructure, and degree of phosphating to form a composite active phase in which phosphides and oxides coexist while maintaining open mass transfer channels and the main structure. This would allow for the catalytic performance of both hydrogen evolution reaction and HMF electrocatalytic oxidation reaction, and make it suitable for a two-electrode electrolysis system in which the two are coupled. Summary of the Invention
[0007] In view of this, the present invention provides an in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst, its preparation method, and its application. The present invention constructs a prismatic Co-Mo-Cu composite oxide precursor by in-situ growth on a conductive substrate, followed by controlled phosphating treatment. Utilizing the synergistic effect between the Co-Mo-Cu metal components, the self-supporting integrated structure, and the regulatory effect of the phosphide on the electronic structure of the oxide, the simultaneous enhancement of HER and HMFOR activities in alkaline media is achieved. Using this catalyst simultaneously as both cathode and anode, a dual-electrode electrolysis system of HMFOR coupled with HER is constructed, enabling the synergistic preparation of hydrogen and the high-value chemical 2,5-furandicarboxylic acid while reducing overall electrolysis energy consumption.
[0008] The first aspect of this invention provides a method for preparing an in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst, comprising the following steps: S1. Dissolve the cobalt source and molybdenum source in water to prepare a Co-Mo metal precursor solution; S2. The conductive substrate copper foam is vertically immersed in the metal precursor solution, and a hydrothermal reaction is carried out under closed conditions to grow a prismatic Co-Mo-Cu composite oxide precursor on the surface of the copper foam in situ. S3. Place the copper foam loaded with the oxide precursor and the phosphorus source downstream and upstream of nitrogen respectively for phosphating treatment to obtain the in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst.
[0009] Preferably, the cobalt source is at least one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, or cobalt sulfate heptahydrate; the molybdenum source is sodium molybdate dihydrate and / or ammonium molybdate heptahydrate.
[0010] Preferably, the molar ratio of cobalt ions to molybdate ions in the Co-Mo metal precursor solution is 1:1, and the concentrations of both cobalt ions and molybdate ions are 40~100 mmol / L.
[0011] Preferably, the hydrothermal reaction is carried out at a temperature of 150–200°C for 6–15 hours. Within this temperature and time range, the hydrothermal reaction provides sufficient energy to overcome the activation energy barrier required for crystal growth, thereby growing a uniform Co-Mo-Cu composite oxide precursor on the conductive substrate. If the reaction temperature is too low or the time is too short, the loading of the active component will be insufficient; if the reaction temperature is too high or the time is too long, the structural integrity of the substrate may be affected.
[0012] Preferably, the phosphorus source is sodium hypophosphite; the mass ratio of the phosphorus source to the loading of the Co-Mo-Cu composite oxide precursor is (1~10):1. During the heat treatment process, the phosphorus source decomposes upon heating to generate phosphorus-containing active gaseous species, which are carried and diffused to the surface of the precursor by a protective gas. There, they undergo an in-situ gas-phase phosphating reaction with the Co-Mo-Cu composite oxide and the copper substrate, controllably generating a phosphating layer on the CoMo oxide surface and a Cu3P phosphide phase, thereby constructing an in-situ composite structure where phosphides and oxides coexist. If the amount of phosphorus source is too small, the total amount of phosphorus-containing active gaseous species will be insufficient, the degree of phosphating reaction will be limited, and it will be difficult to form an effective phosphide-oxide composite interface; if the amount of phosphorus source is too large, it may lead to excessive growth of phosphides, disrupting the synergistic ratio between the multiple components.
[0013] Preferably, the phosphating treatment is performed at a temperature of 300-400℃ for 1-2 hours, with a heating rate of 2-10℃ / min. Under these heat treatment conditions, the phosphorus source can be stably and fully pyrolyzed and diffused onto the precursor surface. Phosphorus-containing active gaseous species undergo a moderate in-situ gas-phase phosphating reaction with the Co-Mo-Cu composite oxide precursor. While preserving the prismatic main morphology, a phosphating layer on the CoMo oxide surface and a Cu3P phosphide phase are controllably generated, forming a phosphide oxide composite structure with abundant heterogeneous interfaces together with CoMoO4 and Cu2O. If the heat treatment temperature is too low or the time is too short, the phosphating reaction will be insufficient, failing to effectively construct the phosphide phase and the corresponding composite interface. If the heat treatment temperature is too high or the time is too long, it may lead to excessive growth of the phosphide phase, disrupting the synergistic ratio between the components.
[0014] A second aspect of the present invention provides an in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst prepared according to the above method, the electrocatalyst comprising a copper foam substrate and a support layer located on the surface of the copper foam substrate, the support layer mainly comprising CoMoO4 and its surface phosphating layer, Cu2O and Cu3P.
[0015] The third aspect of this invention provides the application of the in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst as a cathode and anode in the electrocatalytic oxidation-coupled hydrogen evolution reaction of 5-hydroxymethylfurfural in a two-electrode system and alkaline medium.
[0016] Compared with the prior art, the beneficial technical effects of the present invention are as follows: This invention uses copper foam as a conductive substrate and achieves in-situ growth of a Co-Mo-Cu composite oxide precursor directly on the copper foam surface via a hydrothermal reaction. The copper foam loaded with the precursor is then subjected to a gas-phase phosphating treatment. The resulting catalyst can be used directly as a working electrode without the need to prepare a slurry with catalyst powder, binder, and conductive additives before coating. This creates an integrated connection between the active material and the conductive substrate, which helps shorten the electron transport path and reduce additional contact resistance at the coating interface. Combined with the performance results of the powder-coated comparative example and Example 2 at approximately -100 mA cm⁻¹, this method achieves optimal performance. -2 The test results showing that the current remained basically stable for 25 h of continuous hydrogen evolution at the current density indicate that the self-supporting electrode configuration can balance electrocatalytic activity and continuous working stability.
[0017] The precursor and phosphating catalyst obtained in this invention maintain a three-dimensional structure formed by the interlocking of micron-sized prisms. These prisms have interconnected pores, and moderate phosphating roughens the prism surfaces while preserving the main framework, which is beneficial for electrolyte contact, reactant transport, and exposure of the active surface. Elemental distribution results show that P, Co, Mo, and Cu are uniformly distributed in the prism regions. Phase analysis indicates that the catalyst mainly comprises Cu3P, CoMoO4, and Cu2O phases. By limiting the amount of phosphorus source, phosphating temperature, and phosphating time, the formation of a phosphide-oxide composite active phase can be achieved while avoiding the adverse effects of excessive phosphating on the prism morphology and component ratio.
[0018] This invention utilizes a multi-metallic composition of Co, Mo, and Cu, along with a multiphase composite structure of CoMoO4 and its surface phosphating layer, Cu3P, and Cu2O, to enable the same catalyst to exhibit activity in both alkaline hydrogen evolution reaction and HMF electrocatalytic oxidation reaction. Compared to comparative examples lacking cobalt, lacking molybdenum, unphosphated, only phosphated copper foam, and powder-coated types, the multi-component in-situ composite self-supporting electrode of this invention exhibits superior overall electrocatalytic performance, thereby addressing the problem that a single component or single electrode configuration cannot simultaneously meet the requirements of two reactions.
[0019] The catalyst of this invention can be used as both cathode and anode to construct a dual-electrode system for HMF electrocatalytic oxidation coupled with hydrogen evolution. It can be used in coupled electrolysis over a wide current density range and exhibits stability for continuous operation. The catalyst preparation method of this invention mainly includes two stages: hydrothermal in-situ growth and phosphating under a nitrogen atmosphere. The raw materials used are common, and the process parameters are well-defined, facilitating the preparation of a self-supporting integrated electrode. Furthermore, it provides a material basis for achieving high-value HMF conversion at the anode and at the cathode in the same electrolysis device. Attached Figure Description
[0020] The present invention will be further described below with reference to the accompanying drawings.
[0021] Figure 1 SEM images of the in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalysts prepared in Examples 1-6 of this invention; wherein, a) is Example 1, b) is Example 2, c) is Example 3, d) is Example 4, e) is Example 5, and f) is Example 6; Figure 2 EDS elemental distribution images of the in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst prepared in Example 2 of the present invention, wherein a) is a SEM image of a selected region, b) is a mixed distribution map of P, Co, Cu and Mo, c) is a P elemental distribution image, d) is a Co elemental distribution image, e) is a Cu elemental distribution image, and f) is a Mo elemental distribution image. Figure 3SEM images of the catalysts prepared in Comparative Examples 1 to 6 of the present invention, wherein a) is Comparative Example 1, b) is Comparative Example 2, c) is Comparative Example 3, d) is Comparative Example 4, e) is Comparative Example 5, and f) is Comparative Example 6. Figure 4 The XRD patterns of the in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalysts prepared in Examples 1-6 of this invention are shown below. Figure 5 The XRD patterns of the catalyst samples prepared in Comparative Examples 1-6 of this invention are shown. Figure 6 The figures show the electrocatalytic hydrogen evolution reaction (HER) performance curves of the in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalysts prepared in Examples 1-6 of this invention in 1.0 mol / L KOH electrolyte; where a) is the polarization curve and b) is the corresponding Tafel curve. Figure 7 The HER performance comparison curves of the catalysts prepared in Example 2 and Comparative Examples 1-6 of this invention in 1.0 mol / L KOH electrolyte are shown, where a) is the polarization curve and b) is the corresponding Tafel curve. Figure 8 The HER chronocurrent stability curve of the in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst prepared in Example 2 of this invention in 1.0 mol / L KOH electrolyte at a constant potential of -0.126 V (vs. RHE); Figure 9 The performance curves of the in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst prepared in Examples 1-6 of this invention for HMF electrocatalytic oxidation (HMFOR) in a mixed electrolyte containing 10 mmol / L HMF and 1.0 mol / L KOH. Figure 10 The performance curves of the in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalysts prepared in Examples 1-6 were obtained by performing HMFOR coupled HER reaction in a dual-chamber electrolytic cell in a mixed electrolyte of 1.0 mol / L KOH containing 10 mmol / L HMF and a 1.0 mol / L KOH electrolyte, respectively. Figure 11 The in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst prepared in Example 2 of this invention was subjected to chronocurrent stability curves for the HMFOR coupled HER reaction in a dual-chamber electrolytic cell in a mixed electrolyte of 1.0 mol / L KOH containing 10 mmol / L HMF and a 1.0 mol / L KOH electrolyte, at a constant potential of 1.42 V. Detailed Implementation
[0022] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0023] Example 1: A method for preparing an in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst (denoted as CoMoCuO@CF-P1-1h), the steps of which are as follows: (1) The cut foam copper conductive substrate (size: 30 mm × 30 mm × 1 mm) was completely immersed in acetone and ultrasonically cleaned for 30 min. After taking it out, it was rinsed alternately with deionized water and anhydrous ethanol until there was no acetone residue. Then it was immersed in 1.0 mol / L hydrochloric acid solution and ultrasonically treated for 3 min in an ultrasonic machine with a power of 100 W and a frequency of 40 kHz. After taking it out, it was rinsed alternately with a large amount of deionized water and anhydrous ethanol until the washing solution was neutral. Finally, it was placed in a vacuum drying oven at 60℃ and dried for 12 h to obtain a clean foam copper conductive substrate with a total weight of 0.5087 g. (2) Weigh 0.7259 g of sodium molybdate dihydrate and dissolve it in 30 mL of deionized water; weigh 0.8731 g of cobalt nitrate hexahydrate and dissolve it in 30 mL of deionized water. Mix the two solutions and stir magnetically for 30 min to obtain a homogeneous and transparent metal precursor solution, wherein the concentrations of cobalt ions and molybdate ions are both 50 mmol / L. (3) The metal precursor solution obtained in step (2) was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor. The foamed copper treated in step (1) was vertically immersed in the solution. After sealing the reactor, it was placed in an oven and kept at 180°C for 9 h. After the reaction was completed, it was naturally cooled to room temperature. The foamed copper with active material was taken out and repeatedly rinsed with deionized water to remove impurities and ions attached to the surface. It was dried in a vacuum drying oven at 60°C for 12 h to obtain foamed copper with Co-Mo-Cu composite oxide precursor grown in situ, denoted as CoMoCuO@CF, with a total weight of 0.6089 g, so the precursor loading was about 0.1 g. (4) Weigh 0.1 g of NaH2PO2, which is 1 times the precursor loading, and place it upstream of a tube furnace. Place the CoMoCuO@CF obtained in step (3) downstream of the tube furnace. Introduce nitrogen gas at a flow rate of 40 mL / min. First, purge the gas for 1 h to remove the air from the tube furnace. Then, raise the temperature from room temperature to 350℃ at a rate of 5℃ / min and hold the temperature for 1 h. After the reaction is complete, allow it to cool naturally to room temperature under the same nitrogen conditions to obtain the in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst, denoted as CoMoCuO@CF-P1-1h.
[0024] Example 2 The difference from Example 1 is that the amount of NaH2PO2 used in step (4) is twice the amount of the precursor loading (i.e., 0.2g), and the resulting in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst is denoted as CoMoCuO@CF-P2-1h.
[0025] Example 3 The difference from Example 1 is that the amount of NaH2PO2 used in step (4) is 5 times the amount of precursor loading (i.e. 0.5g), and the resulting in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst is denoted as CoMoCuO@CF-P5-1h.
[0026] Example 4 The difference from Example 1 is that the amount of NaH2PO2 used in step (4) is 10 times the amount of precursor loading (i.e., 1.0g), and the resulting in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst is denoted as CoMoCuO@CF-P10-1h.
[0027] Example 5 The difference from Example 1 is that the amount of NaH2PO2 used in step (4) is twice the amount of the precursor loading (i.e., 0.2g), and the heat preservation reaction time is 2 h. The resulting in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst is denoted as CoMoCuO@CF-P2-2h.
[0028] Example 6 The difference from Example 1 is that the amount of NaH2PO2 used in step (4) is 5 times the amount of precursor loading (i.e. 0.5g), and the heat preservation reaction time is 2 h. The resulting in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst is denoted as CoMoCuO@CF-P5-2h.
[0029] Comparative Example 1 The difference from Example 2 is that sodium molybdate dihydrate is not added in step (2), but only 0.8731 g of cobalt nitrate hexahydrate is added. The resulting in-situ composite Co-Cu-based phosphide oxide self-supporting electrocatalyst is denoted as CoCuO@CF-P2-1h.
[0030] Comparative Example 2 This comparative example provides a method for preparing an in-situ composite Mo-Cu-based phosphide oxide self-supporting electrocatalyst (denoted as MoCuO@CF-P2-1h). The difference from Example 2 is that cobalt nitrate hexahydrate is not added in step (2), but only 0.7259 g of sodium molybdate dihydrate is added.
[0031] Comparative Example 3 The difference from Example 2 is that the phosphating treatment in step (4) is omitted, that is, the Co-Mo-Cu composite oxide precursor is directly obtained after hydrothermal reaction. The remaining steps and parameters are the same as in Example 2. The in-situ composite Co-Mo-Cu oxide self-supporting electrocatalyst is denoted as CoMoCuO@CF.
[0032] Comparative Example 4 The difference from Example 2 is that steps (2) and (3) are omitted, and the clean foam copper substrate after step (1) is directly subjected to phosphating treatment according to the conditions of step (4) of Example 2; the amount of phosphorus source is 0.2 g NaH2PO2 according to the amount used in Example 2, and the resulting in-situ composite Cu-based phosphide oxide self-supporting electrocatalyst is denoted as CuO@CF-P2-1h.
[0033] Comparative Example 5 The difference from Example 2 is that: in step (3), the copper foam substrate is not added for hydrothermal reaction, the obtained precipitate is separated by centrifugation at 10000 r / min for 5 min, washed 3 times with deionized water and vacuum dried at 60℃ for 12 h to obtain Co-Mo oxide powder precursor; in step (4), the obtained powder precursor is phosphated according to the conditions of step (4) of Example 2 (0.2 g NaH2PO2) to obtain Co-Mo based phosphide oxide powder catalyst; (5) Weigh 5.0 mg of the above-mentioned powdered catalyst and disperse it in a mixed solution consisting of 0.50 mL of deionized water, 0.45 mL of anhydrous ethanol and 0.05 mL of 5 wt% Nafion. Sonicate the solution for 30 min to form a uniform slurry. Then, uniformly drop-coat the slurry onto a clean copper foam conductive substrate (coating area of 10 mm × 10 mm) in several portions. The catalyst surface loading is approximately 5 mg / cm². -2The mixture was dried in a vacuum oven at 60°C for 12 h to obtain a copper foam-supported Co-Mo-based phosphide oxide powder-coated composite electrocatalyst, denoted as CF / CoMoO-P2-1h.
[0034] Comparative Example 6 The difference from Comparative Example 5 is that the powder precursor phosphating treatment in step (4) is omitted; the conductive substrate in step (5) is replaced with the phosphated copper foam prepared in Comparative Example 4, and a Co-Mo-Cu based phosphide oxide powder coated composite electrocatalyst supported on copper foam is obtained, denoted as CF / CoMoCuO-P2-1h.
[0035] Example 1 SEM analysis: Depend on Figure 1 As can be seen, the in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalysts prepared in Examples 1-6 all exhibit a three-dimensional porous network structure formed by overlapping and stacking micron-sized prisms, with abundant micron-sized pore channels between the prisms, exhibiting typical self-supporting integrated electrode structure characteristics. As the amount of phosphorus source increased from 1 times to 10 times the precursor loading (Examples 1-4), the prism surface gradually changed from relatively smooth to rough, and the roughness increased with the degree of phosphating. This surface roughening is expected to provide more exposed active sites for the electrocatalytic reaction. Extending the phosphating holding time (Examples 5 and 6) can also make the prism surface rougher, but excessively high phosphating degrees (Examples 4 and 6) will cause slight corrosion marks on some prism edges, indicating that the degree of phosphating needs to be controlled within an appropriate range to balance morphological integrity and surface activation.
[0036] Depend on Figure 2 It can be seen that in the catalyst (CoMoCuO@CF-P2-1h) obtained in Example 2, P, Co, and Mo exhibit a uniform co-distribution characteristic in the prismatic region, and the distribution profile highly matches the prismatic morphology, proving that P has been successfully introduced into the bulk phase or near-surface region of the oxide prism. In addition to showing a strong signal in the foamed copper substrate region, Cu also shows a uniform distribution in the prismatic region, indicating that copper-containing active species generated in situ on the copper substrate surface during phosphating participate in the composite construction of the prismatic morphology.
[0037] Depend on Figure 3It can be seen that neither Comparative Example 1 (CoCuO@CF-P2-1h, molybdenum-deficient) nor Comparative Example 2 (MoCuO@CF-P2-1h, cobalt-deficient) exhibited a prismatic morphology: the former was a coarse granular aggregate, while the latter was a fine-particle stacked morphology. This indicates that neither a cobalt system nor a molybdenum system alone can induce the formation of a micron-scale prismatic structure. The synergistic effect of the Co-Mo bimetallic compound is a necessary prerequisite for forming the unique prismatic morphology of this invention. Comparative Example 3 (CoMoCuO@CF, unphosphated) also exhibited a relatively regular prismatic stacked morphology. Figure 3 c), whose overall morphology is basically consistent with that of Examples 1-6, indicates that the subsequent phosphating treatment did not destroy the inherent prismatic framework structure of the Co-Mo-Cu composite oxide precursor, providing a good structural basis for introducing phosphorus modification while maintaining a favorable morphology. Comparative Example 4 (CuO@CF-P2-1h, direct phosphating of copper foam without cobalt-molybdenum precursor) only shows the rough and porous surface of the phosphated copper foam substrate. Figure 3 d) This is fundamentally different from the prism morphology, further confirming... Figure 1 The prismatic morphology observed in the samples originated from the in-situ grown Co-Mo-Cu composite oxide precursor, rather than the reaction product of the phosphorus source and the copper substrate. Comparative Example 5 (CF / CoMoO-P2-1h) and Comparative Example 6 (CF / CoMoCuO-P2-1h) both exhibited a morphology composed of a large number of randomly stacked nanoscale elongated or short rod-shaped particles. Figure 3 e, 3f) are significantly different from the micron-sized prism morphology obtained by in-situ hydrothermal growth on the copper foam substrate in Examples 1-6, indicating that the copper foam substrate has an important inducing and confining effect on the formation of oxide prism morphology, while under free growth conditions without substrate constraint, crystals tend to form nanorods along the one-dimensional direction.
[0038] XRD analysis: Depend on Figure 4 It can be seen that the in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalysts prepared in Examples 1-6 exhibit a series of characteristic diffraction peaks in the range of 25°~29°. Figure 5Comparison of the XRD patterns of Comparative Example 3 (the unphosphated Co-Mo-Cu composite oxide precursor) shows that no diffraction peaks of cobalt or molybdenum phosphides appeared after phosphating. Furthermore, the positions of these diffraction peaks highly match those of the CoMoO4 standard card (PDF#00-021-0868), confirming that the catalyst retains the intrinsic crystal phase structure of cobalt-molybdenum oxide after phosphating heat treatment, and the phosphating reaction mainly occurs on its surface and near-surface region. Simultaneously, each sample exhibits strong and sharp characteristic peaks near 43°~45°, corresponding to the diffraction signal of conductive substrate copper foam (PDF#01-071-4609); obvious characteristic peaks appear between 35°~45°, corresponding to the diffraction signal of Cu2O (PDF#01-073-6371); and obvious characteristic peaks exist between 45°~50°, corresponding to the diffraction signal of Cu3P (PDF#00-002-1263). As the amount of phosphorus source increased from 1 to 10 times (Examples 1 to 4), the diffraction peak intensity of the copper foam substrate gradually decreased, while the diffraction peak intensity of Cu3P gradually increased. This indicates that phosphorus-containing active gaseous species reacted gradually with the copper foam substrate on the surface of cobalt molybdenum phosphide oxide. Furthermore, the greater the amount of phosphorus source, the deeper the phosphating of the substrate and the higher the Cu3P content. This trend is consistent with the phenomenon observed by SEM that the surface roughness of the prism intensifies with increasing phosphorus source amount. In summary, the in-situ composite Co-Mo-Cu based phosphide oxide prism-shaped self-supporting electrocatalysts prepared in Examples 1-6 are mainly composed of three crystalline components: Cu3P, CoMoO4, and Cu2O.
[0039] Depend on Figure 5 It can be seen that Comparative Example 1 (CoCuO@CF-P2-1h, containing only cobalt source and phosphated) exhibits characteristic diffraction peaks of Co3O4 in the range of 28°~33° (PDF#04-005-7243), characteristic diffraction peaks of Cu2O in the range of 35°~45° (PDF#01-073-6371), and strong characteristic peak groups of Cu3P in the range of 45°~50°. However, no diffraction signals of any molybdenum-containing phase were detected, indicating that under the condition of lack of molybdenum source, the cobalt species exists in the form of Co3O4 and cannot form the CoMoO4 phase. In the XRD pattern of Comparative Example 2 (MoCuO@CF-P2-1h, containing only molybdenum source and phosphated), no obvious diffraction peaks of molybdenum compound crystallization were observed, indicating that under the condition of lack of cobalt source, the molybdenum source failed to form a phase with good crystallinity (denoted as MoO) after hydrothermal treatment and subsequent phosphated treatment. xIn addition, it contains two crystalline phases, Cu3P and Cu2O, consistent with the amorphous fine particle morphology observed by SEM. Comparative Example 3 (CoMoCuO@CF, unphosphated) exhibits characteristic diffraction peaks of CoMoO4 in the range of 25°~29°, which are basically consistent with the main diffraction peak positions of Examples 1~6. The presence of the Cu2O crystalline phase further confirms that the phosphating treatment did not change the intrinsic crystalline phase structure of the cobalt-molybdenum oxide precursor. In the XRD pattern of Comparative Example 4 (CuO@CF-P2-1h, phosphating treatment only on the copper foam substrate), only a strong diffraction peak group of Cu3P appears in the range of 45°~50°, with no characteristic peaks of CoMoO4 observed, confirming... Figure 3 The rough morphology observed in d is due to the direct reaction between the copper foam substrate and the phosphorus source to form Cu3P, and is not related to the prismatic morphology of the cobalt-molybdenum oxide. The XRD patterns of Comparative Example 5 (CF / CoMoO-P2-1h) and Comparative Example 6 (CF / CoMoCuO-P2-1h) (only the powder product before coating was tested) both show a series of characteristic diffraction peaks consistent with the CoMoO4 standard card (PDF#00-021-0868). The positions of the diffraction peaks are basically the same, corresponding to the crystal phase structure of CoMoO4, indicating that the phosphating treatment (Comparative Example 5) did not change the main crystal phase of the cobalt-molybdenum oxide powder, and the phosphating reaction only occurred on its surface and near-surface region. It is particularly noteworthy that, combined with the elemental distribution analysis results from SEM testing, it can be seen that after controlled phosphating treatment, a phosphating layer forms on the surface of the CoMoO4 species in the catalysts prepared in Examples 1-6.
[0040] Table 1. Differences in key synthetic steps and main phase composition (excluding the copper conductive substrate) of the catalysts prepared in Examples 1-6 and Comparative Examples 1-6
[0041] Example 2 The catalysts prepared in Examples 1-6 and Comparative Examples 1-6 were used as working electrodes to test the performance of the electrocatalytic hydrogen evolution reaction (HER) and the electrocatalytic oxidation of 5-hydroxymethylfurfural (HMFOR) using the catalysts prepared in Examples 1-6 as working electrodes. The specific methods are as follows: (1) Weigh 2.522 g of 5-hydroxymethylfurfural, dissolve it in deionized water and make up to 200 mL to obtain a stock solution of HMF with a concentration of 100 mmol / L; (2) Weigh 5.611 g of potassium hydroxide solid, dissolve it in deionized water and dilute to 100 mL to obtain a KOH solution with a concentration of 1.0 mol / L. Weigh another 5.611 g of potassium hydroxide solid, dissolve it in deionized water, accurately transfer 10 mL of the HMF stock solution obtained in step (1), and transfer it to a 100 mL volumetric flask. Dilute to volume with deionized water to obtain a mixed electrolyte containing 10 mmol / L HMF and 1.0 mol / L KOH. (3) HER test: A standard three-electrode system was used at room temperature, with the prepared catalyst directly used as the working electrode (geometric area 1 cm²). 2 The electrode setup used a graphite carbon rod as the counter electrode, a mercury / mercury oxide (Hg / HgO) electrode as the reference electrode, and a 1.0 mol / L KOH solution as the electrolyte. HMFOR assay: At room temperature, an H-type dual-chamber electrolytic cell was used, with Fumasep FAA-3-50 as the ion exchange membrane, the prepared catalyst as the working electrode, a graphite carbon rod as the counter electrode, and a saturated Ag / AgCl electrode as the reference electrode. A 1.0 mol / L KOH solution was added to the cathode chamber, and a mixed electrolyte of 1.0 mol / L KOH containing 10 mmol / L HMF was added to the anode chamber. HER and HMFOR coupling assay: Using the prepared catalyst as both the cathode and anode, the above-mentioned H-type dual-chamber electrolytic cell was used. The cathode chamber contained a 1.0 mol / L KOH solution, and the anode chamber contained a mixed electrolyte of 1.0 mol / L KOH containing 10 mmol / L HMF. A constant potential electrolysis was performed on the two-electrode system.
[0042] The linear scan voltammetry test was conducted at a scan rate of 10 mV / s, with a scan potential range of 0.1–0.8 V. All electrode potentials were converted to their values relative to the reversible hydrogen electrode (RHE) using the Nernst equation. Before the formal test, each working electrode underwent six cyclic voltammetric scans at a scan rate of 100 mV / s within its potential window to complete the activation process, ensuring stable and reliable test results.
[0043] Electrocatalytic hydrogen evolution (HER) performance: Figure 6 The figures show the HER performance curves of the catalysts prepared in Examples 1-6 in a 1.0 mol / L KOH electrolyte. Figure 6 a) is the polarization curve (LSV). Figure 6 b) is the corresponding Tafel curve; Figure 7 The figures show the HER performance comparison curves of the catalysts prepared in Example 2 and Comparative Examples 1-6 under the same conditions. Figure 7 a) is the polarization curve. Figure 7 b) is the corresponding Tafel curve. Figure 8The chronocurrent (it) stability curve of the catalyst prepared in Example 2 at a constant potential of -0.126 V (vs. RHE) in 1.0 mol / L KOH electrolyte is shown.
[0044] Depend on Figure 6 As can be seen, the in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalysts prepared in Examples 1-6 all exhibited excellent HER catalytic activity in 1.0 mol / L KOH electrolyte, with each polarization curve showing a typical rapid rise characteristic. The overpotential data of each example at different current densities are listed in Table 2.
[0045] Table 2. Overpotentials required for electrocatalytic HER of the catalysts prepared in Examples 1-6 at different current densities.
[0046] As shown in Table 2, Example 2 (CoMoCuO@CF-P2-1h) exhibited the best hydrogen evolution performance at 10, 50, 100, and 200 mA cm⁻¹. -2 The required overpotentials at the current densities were only 17 mV, 96 mV, 126 mV, and 166 mV, respectively. As the amount of phosphorus source increased sequentially from 1 times (Example 1) to 2 times (Example 2), 5 times (Example 3), and 10 times (Example 4), the required overpotential of the catalyst showed a trend of first decreasing and then increasing. This indicates that appropriate phosphating treatment is beneficial for constructing the optimal phosphide-oxide composite interface. Too little phosphorus source will result in insufficient phosphide phase formation, while too much phosphorus source may lead to excessive phosphide growth and disrupt the synergistic ratio between the components.
[0047] Depend on Figure 6 As can be seen from b, the Tafel curves of all embodiments exhibit a good linear relationship. Among them, the Tafel slope of Example 2 (CoMoCuO@CF-P2-1h) is the lowest, at only 61.2 mV dec. -1 This is significantly superior to other embodiments, indicating that the catalyst exhibits the fastest hydrogen evolution reaction kinetics and the lowest energy barrier to be overcome for its rate-determining step. The Tafel slope value suggests that the HER reaction follows the Volmer-Heyrovsky mechanism.
[0048] Depend on Figure 7As can be seen, Example 2 requires the lowest overpotential at the same current density, exhibiting the best hydrogen evolution activity. The above comparative results indicate that the synergistic effect of the Co-Mo-Cu based phosphide oxide components is a necessary condition for achieving high hydrogen evolution activity. Component deficiency or changes in electrode configuration (Comparative Examples 1-6) both lead to catalyst activity degradation, and the performance loss caused by the absence of cobalt components (Comparative Example 2) is more significant than that caused by the absence of molybdenum components (Comparative Example 1). Controllable phosphating of the cobalt-molybdenum oxide precursor to construct a phosphide oxide composite structure can significantly improve the hydrogen evolution activity of the catalyst; omitting the phosphating treatment (Comparative Example 3) results in a significant performance degradation, confirming the crucial role of constructing the Cu3P / CoMoO4 / Cu2O composite interface in improving hydrogen evolution performance. The catalyst obtained by phosphating the copper foam substrate alone (Comparative Example 4) exhibits the worst hydrogen evolution activity, indicating that in the absence of cobalt-molybdenum bimetallic components, generating only the Cu3P phase cannot effectively optimize the catalytic hydrogen evolution activity of the material. Compared with powder-coated catalysts (Comparative Examples 5 and 6), the in-situ grown self-supporting prismatic integrated electrode of Example 2 exhibited lower overpotential and superior mass transfer performance across the entire current density range. This is mainly attributed to the abundant heterogeneous interfaces formed between Cu3P, CoMoO4, and Cu2O, which promoted interfacial charge transfer and generated a synergistic enhancement effect. Simultaneously, it effectively avoided the problems of increased interfacial resistance and active site burial caused by the use of binders in traditional coated electrodes.
[0049] Depend on Figure 7 b shows that the Tafel slope in Example 2 is 61.2 mV dec. -1 It is significantly lower than that of Comparative Example 1 (105.1 mV dec). -1 Comparative Example 2 (119.5 mV dec) -1 Comparative Example 3 (132.3 mV dec) -1 Comparative Example 4 (122.4 mV dec) -1 Comparative Example 5 (116.9 mV dec) -1 ) and Comparative Example 6 (197.5 mV dec -1 This further confirms that the in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst prepared in Example 2 exhibits the fastest hydrogen evolution reaction kinetics. Combined polarization curves and Tafel analysis results show that the synergistic effect between Co-Mo-Cu metal sites and the construction of the phosphide oxide composite structure are both indispensable, jointly endowing the catalyst of this invention with excellent intrinsic hydrogen evolution activity and rapid reaction kinetics.
[0050] Depend on Figure 8It can be seen that the in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst prepared in Example 2 maintained a current density of approximately -100 mA cm⁻¹ throughout the continuous HER test for up to 25 h. -2 The current density remained relatively stable, with only a current drop of about 11.7%, indicating that the catalyst possesses excellent electrocatalytic stability under high current density and prolonged alkaline hydrogen evolution conditions. Therefore, the in-situ growth method employed in this invention directly constructs a phosphide oxide composite prism structure on the surface of a copper foam conductive substrate. The resulting integrated self-supporting electrode structure effectively prevents the shedding of the active phase during long-term electrolysis and vigorous hydrogen evolution, providing strong support for its industrial application.
[0051] HMF electrocatalytic oxidation (HMFOR) performance: Figure 9 Electrocatalytic HMFOR performance curves of the catalysts prepared in Examples 1-6 in a mixed electrolyte containing 10 mmol / L 5-hydroxymethylfurfural and 1.0 mol / L potassium hydroxide.
[0052] Table 3. Potential values required for electrocatalytic HMFOR of the catalysts prepared in Examples 1-6 at different current densities.
[0053] Depend on Figure 9 As shown in Table 3, the in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalysts prepared in Examples 1-6 all exhibited excellent HMFOR activity in alkaline electrolytes containing HMF. Among them, Example 2 (CoMoCuO@CF-P2-1h) showed particularly good activity at 50 and 100 mA cm⁻¹. -2 The required potentials are 1.45 V and 1.56 V, respectively, lower than in other embodiments; at 200 mA cm⁻¹ -2 The required potential is 1.61 V, the same as in Example 4; at 10 mA cm⁻¹ -2At that time, its potential was 1.33V, which is at a relatively low level. Considering the overall performance over a wide current density range, Example 2 exhibited superior HMFOR activity. The above results indicate that controlled phosphating treatment with a phosphorus source dosage of 2 times the mass ratio and a holding time of 1 h can achieve a good balance between the construction of the Cu3P / CoMoO4 / Cu2O composite structure and the integrity of the prismatic morphology, effectively optimizing the adsorption behavior of HMF molecules and their oxygen-containing intermediates at the active sites, thereby endowing the catalyst with balanced and excellent HMFOR activity over a wide current density range. When the phosphorus source dosage is too low (Example 1), the phosphide oxide composite interface is insufficiently constructed; when the phosphorus source dosage is too high (Example 4) or the holding time is prolonged (Examples 5 and 6), it is not conducive to the continuous improvement of HMFOR activity.
[0054] HMFOR coupled HER dual-electrode electrolysis performance: Figure 10 To use the catalysts prepared in Examples 1-6 as both cathode and anode, polarization curves of the HMFOR coupled HER reaction were obtained in a dual-chamber electrolytic cell with a 1.0 mol / L KOH electrolyte containing 10 mmol / L HMF on the anode side and a 1.0 mol / L KOH electrolyte on the cathode side. Figure 11 The chronocurrent stability curves of the catalyst prepared in Example 2 were obtained by performing the HMFOR coupled HER reaction in the same dual-chamber electrolytic cell at a constant potential of 1.42 V.
[0055] Depend on Figure 10 As shown in Table 4, the dual-electrode coupling systems constructed in Examples 1-6 all achieve significant current responses at relatively low tank voltages. Specifically, Example 4 achieves significant current responses at 50, 100, and 200 mA cm⁻¹. -2 The required cell voltages were 1.53 V, 1.72 V, and 1.82 V, respectively, all of which were the lowest values in each embodiment; Example 2 used 100 and 200 mA cm⁻¹. -2 The required cell voltages are 1.75V and 1.83V, respectively, which are close to those in Example 4 at high current densities. Furthermore, each example operates at 100 mA cm⁻¹. -2 The coupling potential of most of them is lower than the cell voltage of traditional water electrolysis systems (usually >1.8 V), indicating that using the catalyst of this invention to replace OER with HMFOR has the potential to reduce the cell voltage.
[0056] Table 4. Cell voltage required for electrocatalytic HMFOR coupling HER of the catalysts prepared in Examples 1-6 at different current densities.
[0057] Depend on Figure 11As can be seen, the in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst prepared in Example 2 underwent continuous coupled electrolysis testing at a constant potential of 1.42 V for approximately 20 h. The peak current of HMF oxidation and the background current of oxygen evolution remained stable throughout, without significant attenuation. This indicates that the catalyst has good structural integrity and performance durability in the long-term electrolysis of HMFOR coupled with HER, providing strong support for its potential industrial application.
[0058] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing an in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst, characterized in that, Includes the following steps: S1. Dissolve the cobalt source and molybdenum source in water to prepare a Co-Mo metal precursor solution; S2. The conductive substrate copper foam is vertically immersed in the metal precursor solution, and a hydrothermal reaction is carried out under closed conditions to grow a prismatic Co-Mo-Cu composite oxide precursor on the surface of the copper foam in situ. S3. Place the copper foam loaded with the oxide precursor and the phosphorus source downstream and upstream of a nitrogen atmosphere, respectively, for phosphating treatment to obtain the in-situ composite Co-Mo-Cu based phosphide oxide prismatic self-supporting electrocatalyst.
2. The method for preparing an in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst according to claim 1, characterized in that, The cobalt source is at least one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, or cobalt sulfate heptahydrate; the molybdenum source is sodium molybdate dihydrate and / or ammonium molybdate heptahydrate.
3. The method for preparing an in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst according to claim 1, characterized in that, The molar ratio of cobalt ions to molybdate ions in the Co-Mo metal precursor solution is 1:1, and the concentrations of both cobalt ions and molybdate ions are 40~100 mmol / L.
4. The method for preparing an in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst according to claim 1, characterized in that, The hydrothermal reaction is carried out at a temperature of 150~200℃ for a time of 6~15 h.
5. The method for preparing an in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst according to claim 1, characterized in that, The phosphorus source is sodium hypophosphite; the ratio of the mass of the phosphorus source to the loading of the Co-Mo-Cu composite oxide precursor is (1~10):
1.
6. The method for preparing an in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst according to claim 1, characterized in that, The phosphating treatment is performed at a temperature of 300-400℃ for 1-2 hours, with a heating rate of 2-10℃ / min.
7. An in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst, characterized in that, The electrocatalyst comprises a copper foam substrate and a supported layer on the surface of the copper foam substrate. The supported layer mainly comprises CoMoO4 and its surface phosphating layer, Cu2O and Cu3P. The catalyst is prepared by the method according to any one of claims 1 to 6.
8. The application of an in-situ composite Co-Mo-Cu-based phosphide oxide prismatic self-supporting electrocatalyst as both cathode and anode in the electrocatalytic oxidation of 5-hydroxymethylfurfural coupled with hydrogen evolution in a two-electrode system and alkaline medium, characterized in that... The catalyst is prepared by the method described in any one of claims 1 to 6.
Citation Information
Patent Citations
Full-hydrolysis device adopting electrooxidation of 5-hydroxymethylfurfural as anodic reaction, and reaction method thereof
CN110205645A
Method for preparing 2, 5-furandicarboxylic acid by electro-catalyzing oxidation of 5-hydroxymethylfurfural and simultaneously electrolyzing water to prepare hydrogen
CN112538636A
Foamed nickel self-supporting FeCo phosphide electrocatalyst, preparation method and application thereof
CN112774704A